Numerical Study of the Dynamic Compaction Process considering the Phenomenon of Particle Breakage - Xi Li; Jing Li; Xinyan Ma; Jidong Teng; Sheng Zhang (Advances in Civil Engineering)
Dynamic compaction (DC) is commonly used to strengthen the coarse grained soil foundation, where particle breakage of coarse soils is unavoidable under high-energy impacts. In this paper, a novel method of modeling DC progress was developed, which can realize particle breakage by impact stress. A particle failure criterion of critical stress is first employed. The “population balance” between particles before and after crushing is guaranteed by the overlapping method. The performance of the DC model is successfully validated against literature data. A series of DC tests were then carried out. The effect of particle breakage on key parameters of DC including crater depth and impact stress was discussed. Besides, it is observed that the relationship between breakage amount and tamping times can be expressed by a logarithmic curve. The present method will contribute to a better understanding of DC and benefit further research on the macro-micro mechanism of DC.